2002
DOI: 10.1002/1522-2683(200204)23:7/8<1203::aid-elps1203>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

IgM are associated to Spα (CD5 antigen-like)

Abstract: In 1993, we reported the presence of an IgM-associated peptide (M(r) 44 kDa; pI 5.45) in all immunoglobulin M (IgM) fractions purified from plasma/serum by various methods. This peptide was absent in Ig fractions of non-IgM isotypes. The N-terminal sequence was determined as being APPSGVRLVGGLH. To gain insight into the nature of this peptide, we further analyzed, using modern proteomic tools, the IgM-associated peptide isolated from cryoglobulins. Mass spectrometry revealed three peptides of different masses:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 11 publications
3
30
0
Order By: Relevance
“…PMF analysis allowed us to identify groups (c), (a´) and (d) as IgM or IgM precursor. Similarly, comparison of our 2-DE results to previously reported 2-DE maps of emerald rockcod, brown trout Salmo trutta and human IgMs (Hordvik et al, 2002;Pucci et al, 2003;Tissot et al, 1994Tissot et al, , 2002 suggested that the spots found in group (b) and (b¢) represent the light chain of olive flounder IgM. In addition, the spots found in group (d) were thought to be m chain fragments of IgM induced by freezing, as previously seen in IgM cryoglobulin from human and hybrid bass (Tissot et al, 1994(Tissot et al, , 2002Nitzan et al, 2003).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…PMF analysis allowed us to identify groups (c), (a´) and (d) as IgM or IgM precursor. Similarly, comparison of our 2-DE results to previously reported 2-DE maps of emerald rockcod, brown trout Salmo trutta and human IgMs (Hordvik et al, 2002;Pucci et al, 2003;Tissot et al, 1994Tissot et al, , 2002 suggested that the spots found in group (b) and (b¢) represent the light chain of olive flounder IgM. In addition, the spots found in group (d) were thought to be m chain fragments of IgM induced by freezing, as previously seen in IgM cryoglobulin from human and hybrid bass (Tissot et al, 1994(Tissot et al, , 2002Nitzan et al, 2003).…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, PMF followed by NCBI database searching identified the heavy chains of Ig proteins as IgM or IgM precursor. Previously, 2-DE analysis was used to divide human IgM cryoglobulin (proteins precipitated from plasma or serum at low temperatures and resolubilized by warming) into 5 groups: m chain of IgM (pI 5.6 -6.4, 80 kDa), m chain fragments of IgM, SPa, J-chain and light chain (Tissot et al, 1994(Tissot et al, , 2002. On the other hand, degradation of IgM due to freezing shock was observed in hybrid bass (Morone saxatilis ¥ M. chrysops) by SDS-PAGE analysis (Nitzan et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…This evidence supports the hypothesis that CD5L has a role in the immune system as well as in the interaction with IgM. 14 Tissot et al 14 also report that CD5L is associated with IgM; however, the interaction between the two proteins is not clear. This report is supported by our finding of high correlation between the two proteins.…”
Section: Immune Responsesupporting
confidence: 60%
“…Using 2-DE analyses and MS, we also recently identified a new peptide, called hSpa or CD5L [50]. This peptide was only found when IgM were present, like in cryoglobulins (Fig.…”
Section: Clinical Applications -Biomarker Identificationmentioning
confidence: 91%